Literature Review: Networks, Collaborative Technology and the Internet of Things Impact on Business - Devi Savira Sanurya; Agussalim Agussalim (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
A network is a collection of interconnected devices that aim to share data and resources. With the development of science and various technological collaborations in this digital era, it brings many benefits and real changes to all aspects of life. Work that used to be done by humans has now been gradually replaced by sophisticated technology and adequate internet, resulting in the difficulty of getting a job and increasing unemployment rates. This literature review aims to analyze and classify the networks, collaborative technology and the internet of things impact on business. The development of technology and digitalization can never be avoided, but we can live side by side by using it wisely and utilizing it well.